Solar cell

By adopting a composite electrode structure in TOPCon solar cells and using a specific ratio of ohmic contact layer and conductive layer, the etching problem of the silver paste electrode on the doped polysilicon layer is solved, achieving higher photoelectric conversion efficiency and reducing preparation time. cost.

CN119342906APending Publication Date: 2025-01-21ZHEJIANG JINKO NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411411642.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The electrode made of silver paste etching on the doped polysilicon layer is severely caused by high contact resistance, which limits the improvement of the photoelectric conversion efficiency of TOPCon solar cells.

Method used

A composite electrode structure is adopted, in which the ohmic contact layer is located between the doped polysilicon layer and the conductive layer. The thickness ratio of the ohmic contact layer and the conductive layer is controlled within the range of 1: (1.5~4.5). The ohmic contact layer is composed of a specific ratio of conductive It is made of phase, bonding phase, organic phase and functional additives. The conductive phase contains silver powder, organic silver salt and ohmic contact metal.

Benefits of technology

The degree of etching of the doped polysilicon layer is reduced, and good ohmic contact and conductivity are achieved, thereby improving the photoelectric conversion efficiency of the solar cell and reducing the preparation cost of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of photovoltaic technology, in particular to a solar cell. The solar cell comprises a silicon substrate, and a tunneling oxide layer, a doped polycrystalline silicon layer and a composite electrode which are sequentially arranged on the silicon substrate, the composite electrode comprises an ohmic contact layer and a conductive layer, the ohmic contact layer is located between the doped polycrystalline silicon layer and the conductive layer, and the thickness ratio of the ohmic contact layer to the conductive layer is 1: (1.5-4.5); the ohmic contact layer comprises the following raw materials in percentage by mass: 60%-88% of a conductive phase, 0.5%-6% of a binding phase, 5%-32% of an organic phase and 0-5% of a functional aid; the conductive phase comprises silver powder, organic silver salt and ohmic contact metal in a mass ratio of (45-75): (0.5-5): (5-35), and the conductivity of the ohmic contact metal is lower than that of the silver powder. The composite electrode in the solar cell can realize good ohmic contact and good conductive effect, so that the cell efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photovoltaic technology, and in particular to a solar cell. Background Art

[0002] In the photovoltaic field, TOPCon solar cells, that is, N-type crystalline silicon solar cells with tunnel oxide passivated contact (TOPCon) structure, have a stacked tunnel oxide layer and a doped polysilicon layer on the surface of the silicon wafer, which together form a passivated contact structure. The passivated contact structure provides good surface passivation and field passivation. The tunnel oxide layer allows electrons to tunnel into the doped polysilicon layer and blocks minority holes, greatly reducing the recombination rate of carriers. The lateral transmission characteristics of the doped polysilicon layer reduce the series resistance, thereby improving the open circuit voltage, short circuit current and photoelectric conversion efficiency of the TOPCon solar cell.

[0003] In the preparation process of TOPCon solar cells, conductive pastes such as silver paste are usually used to prepare electrodes through processes such as screen printing and high-temperature sintering. However, the electrodes made of silver paste severely etch the doped polysilicon layer, resulting in high contact resistance, which limits the improvement of the photoelectric conversion efficiency of TOPCon solar cells. Summary of the invention

[0004] Based on this, it is necessary to provide a solar cell to solve the problem that the electrode made of silver paste seriously etches the doped polysilicon layer, resulting in high contact resistance and limiting the improvement of the photoelectric conversion efficiency of the TOPCon solar cell.

[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:

[0006] In a first aspect of the present application, a solar cell is provided, comprising a silicon substrate, and a tunneling oxide layer, a doped polysilicon layer and a composite electrode sequentially disposed on at least one surface of the silicon substrate;

[0007] The composite electrode comprises an ohmic contact layer and a conductive layer, wherein the ohmic contact layer is located between the doped polysilicon layer and the conductive layer, and a thickness ratio of the ohmic contact layer to the conductive layer is 1:(1.5-4.5);

[0008] The ohmic contact layer comprises the following raw materials in mass fractions: 60% to 88% of a conductive phase, 0.5% to 6% of a bonding phase, 5% to 32% of an organic phase, and 0% to 5% of a functional additive;

[0009] The conductive phase includes silver powder, organic silver salt and ohmic contact metal in a mass ratio of (45-75): (0.5-5): (5-35), and the conductivity of the ohmic contact metal is lower than that of the silver powder.

[0010] In one embodiment, the ohmic contact metal includes one or more of zinc, aluminum, molybdenum, tantalum, titanium and tungsten.

[0011] In one embodiment, the organic silver salt includes one or more of silver acetate, silver trifluoroacetate, silver stearate, silver oleate, neodecanoic acid and phenyl silver.

[0012] In one embodiment, the thickness of the ohmic contact layer is 0.6 μm to 1.5 μm, and the thickness of the conductive layer is 1.5 μm to 4.5 μm.

[0013] In one embodiment, the organic phase comprises resin, solvent and plasticizer in a mass ratio of (0.85-4.35):(95.35-99.05):(0.1-0.3).

[0014] In one embodiment, the resin includes one or more of polyvinyl formal, polyvinyl butyral, polyethylene terephthalate, polymethyl methacrylate, ethyl cellulose, hydroxypropyl cellulose, cellulose acetate propionate, cellulose acetate butyrate and styrene resin.

[0015] In one embodiment, the solvent includes one or more of diethylene glycol butyl ether acetate and 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate.

[0016] In one embodiment, the plasticizer includes one or more of dimethyl phthalate, dimethyl adipate and hydrogenated castor oil.

[0017] In one embodiment, the binder phase includes the following components in mass fractions: PbO 20%-40%, Bi2O3 10%-30%, CuO 5%-10%, SiO2 10%-20% and B2O3 15%-30%.

[0018] In one embodiment, the median particle size of the binder phase is 0.5 μm to 1.5 μm.

[0019] In one embodiment, the softening point of the adhesive phase is 250°C to 620°C.

[0020] In one embodiment, the functional additives include one or more of a release agent, a thixotropic agent, a defoaming agent, a dispersant, a leveling agent and an antioxidant.

[0021] In one embodiment, the method for preparing the ohmic contact layer comprises the following steps:

[0022] Providing an ohmic slurry containing a conductive phase, a bonding phase, an organic phase and a functional additive;

[0023] The ohmic paste is screen-printed, dried and sintered to form the ohmic contact layer.

[0024] In one embodiment, the conductive layer includes a silver layer, and the preparation method of the silver layer includes one or more of a sputtering coating method and an electroplating method.

[0025] This application has at least the following beneficial effects:

[0026] In the solar cell provided in the present application, the composite electrode includes an ohmic contact layer and a conductive layer. The ohmic contact layer is located between the doped polysilicon layer and the conductive layer, and the thickness ratio of the two is controlled within the range of 1: (1.5~4.5). This can reduce the degree of etching of the doped polysilicon layer, achieve good ohmic contact and good conductivity at the same time, thereby improving the photoelectric conversion efficiency of the solar cell.

[0027] Among them, the ohmic contact layer is made of a conductive phase, a bonding phase, an organic phase and a functional additive in a specific ratio, and the conductive phase introduces an appropriate amount of ohmic contact metal and organic silver salt on the basis of silver powder. The conductivity of the ohmic contact metal is lower than that of the silver powder, and the difference with the conductivity of the doped polysilicon layer is small, which can reduce the contact resistance between the ohmic contact layer and the polysilicon layer, thereby achieving good ohmic contact, and its price is low, which is conducive to reducing the cost of the ohmic contact layer. As a sintering initiator, the organic silver salt will be converted into highly reactive silver atoms during sintering, which can drive the diffusion of silver in the entire sintering process, accelerate the overall reaction speed, thereby reducing resistance, and avoiding the problem of excessive series resistance caused by the introduction of ohmic contact metal. The organic silver salt can also be dissolved in the organic phase, which is conducive to achieving uniform distribution in the entire system, and the initiation effect during sintering is better, so that the ohmic contact layer has good uniformity and low series resistance. DETAILED DESCRIPTION

[0028] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0030] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0031] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.

[0032] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0033] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.

[0034] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0035] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.

[0036] the term

[0037] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0038] Ohmic contact metal: Ohmic contact is a low-resistance contact formed between metal and semiconductor. The current-voltage characteristic at the contact interface is linear, which can ensure efficient transmission of current between metal and semiconductor, reduce contact resistance, and improve device performance and reliability. Ohmic contact metal refers to metal that can form ohmic contact with semiconductors. Different semiconductor materials and device structures require different ohmic contact metals.

[0039] The electrodes of TOPCon solar cells include the front main grid, front fine grid, back main grid and back fine grid. The main functions of the front fine grid and back fine grid are to form a good ohmic contact with the semiconductor and collect the photogenerated carriers generated by the cell, while the main functions of the front main grid and back main grid are to collect the photogenerated carriers of the fine grid and conduct them out to form current transmission.

[0040] In the preparation process of TOPCon solar cells, conductive pastes such as silver paste are usually used to prepare electrodes through processes such as screen printing and high-temperature sintering. On the one hand, the price of silver paste is expensive, which leads to high costs of TOPCon solar cells. On the other hand, the electrodes made of silver paste severely etch the doped polysilicon layer, resulting in high contact resistance, which limits the improvement of the photoelectric conversion efficiency of TOPCon solar cells.

[0041] Double-sided poly technology is an important direction for TOPCon solar cells to reduce costs and improve efficiency. It effectively improves the photoelectric conversion efficiency of the cell by depositing doped polysilicon (poly-Si) layers on both the front and back of the cell. At the same time, the contact problem between the electrode and the doped polysilicon layer is more prominent. Therefore, for TOPCon solar cells, especially double-sided poly solar cells, how to reduce the contact resistance between the electrode and the doped polysilicon layer is a key issue in achieving cost reduction and efficiency improvement.

[0042] Based on this, in the first aspect of the present application, a solar cell is provided to solve the problem that the electrode made of silver paste seriously etches the doped polysilicon layer, resulting in high contact resistance, which limits the improvement of the photoelectric conversion efficiency of the TOPCon solar cell.

[0043] In some embodiments, a solar cell includes a silicon substrate, and a tunneling oxide layer, a doped polysilicon layer, and a composite electrode sequentially disposed on at least one surface of the silicon substrate;

[0044] The composite electrode includes an ohmic contact layer and a conductive layer, the ohmic contact layer is located between the doped polysilicon layer and the conductive layer, and the thickness ratio of the ohmic contact layer to the conductive layer is 1:(1.5-4.5);

[0045] The ohmic contact layer includes the following raw materials in mass fractions: 60% to 88% of a conductive phase, 0.5% to 6% of a bonding phase, 5% to 32% of an organic phase, and 0% to 5% of a functional additive;

[0046] The conductive phase includes silver powder, organic silver salt and ohmic contact metal in a mass ratio of (45-75): (0.5-5): (5-35), and the conductivity of the ohmic contact metal is lower than that of the silver powder.

[0047] In the solar cell provided in the present application, the composite electrode includes an ohmic contact layer and a conductive layer. The ohmic contact layer is located between the doped polysilicon layer and the conductive layer, and the thickness ratio of the two is controlled within the range of 1: (1.5~4.5). This can reduce the degree of etching of the doped polysilicon layer, achieve good ohmic contact and good conductivity at the same time, thereby improving the photoelectric conversion efficiency of the solar cell.

[0048] Among them, the ohmic contact layer is made of a conductive phase, a bonding phase, an organic phase and a functional additive in a specific ratio, and the conductive phase introduces an appropriate amount of ohmic contact metal and organic silver salt on the basis of silver powder. The conductivity of the ohmic contact metal is lower than that of the silver powder, and the difference with the conductivity of the doped polysilicon layer is small, which can reduce the contact resistance between the ohmic contact layer and the polysilicon layer, thereby achieving good ohmic contact. As a sintering initiator, the organic silver salt will be converted into highly reactive silver atoms during the sintering process, which can drive the diffusion of silver in the entire sintering process, accelerate the overall reaction speed, thereby reducing resistance and avoiding the problem of excessive series resistance caused by the introduction of ohmic contact metal. In addition, the organic silver salt can be dissolved in the organic phase, which is conducive to uniform distribution in the entire system, and the initiation effect during sintering is better, which effectively reduces the series resistance of the battery.

[0049] In the present application, the composite electrode includes an ohmic contact layer and a conductive layer stacked in sequence, the ohmic contact layer contains a bonding phase (i.e., glass powder) with an etching effect, and the conductive layer can be formed by directly sputtering or electroplating a conductive metal without adding a bonding phase, so that the content of the bonding phase per unit area of ​​the composite electrode is significantly reduced, thereby effectively reducing the etching depth of the doped polysilicon layer and improving the contact effect between the composite electrode and the doped polysilicon layer. The potential barrier between the ohmic contact layer and the doped polysilicon layer is small, and it is easy to achieve good ohmic contact; the conductive layer has good conductivity and very low resistance, which is convenient for signal transmission. By controlling the thickness ratio of the ohmic contact layer and the conductive layer, a balance can be achieved between the ohmic contact effect and the conductive performance, while achieving a good ohmic contact effect, avoiding excessive series resistance and reducing the preparation cost of the composite electrode.

[0050] As an example, the thickness ratio of the ohmic contact layer and the conductive layer is 1:(1.5~4.5), such as 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4, 1:4.2 or 1:4.5, and can be further optionally 1:(2.5~3.5).

[0051] Optionally, the thickness of the ohmic contact layer is 0.6 μm to 1.5 μm, for example, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm or 1.5 μm, further optionally 0.8 μm to 1.2 μm, further optionally 1 μm.

[0052] By controlling the thickness of the ohmic contact layer within the range of 0.6μm~1.5μm, it is possible to avoid the inability to achieve the ohmic contact effect due to the thickness being too small, and to avoid the series resistance being too high due to the thickness being too large, thereby achieving the effect of improving the photoelectric conversion efficiency of solar cells. At the same time, due to the low thickness of the ohmic contact layer, the content of the bonding phase (i.e., glass powder) per unit area is reduced, thereby effectively reducing the etching depth of the doped polysilicon layer, which is beneficial to the improvement of the open circuit voltage.

[0053] Optionally, the thickness of the conductive layer is 1.5 μm to 4.5 μm, for example, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm or 4.5 μm.

[0054] Controlling the thickness of the conductive layer within the range of 1.5μm~4.5μm can avoid the situation where the thickness is too small and the conductivity of the composite electrode cannot be guaranteed, and avoid the situation where the thickness is too large and the amount of raw materials and preparation costs are increased, thereby reducing costs and increasing efficiency.

[0055] The composite electrode provided in the present application can be applied to the front fine grid and / or the back fine grid of the solar cell to reduce the contact resistance and achieve good ohmic contact. If the composite electrode is applied to the front fine grid of the solar cell, the thickness of the conductive layer is 2.5μm~4.5μm, further optionally 3μm~4μm, and further optionally 3.5μm. If the composite electrode is applied to the back fine grid of the solar cell, the thickness of the conductive layer is 1.5μm~3.5μm, further optionally 2μm~3μm, and further optionally 2.5μm.

[0056] Optionally, the composite electrode is applied to the front fine grid, and its total thickness is 3.1μm~6μm, further optionally 3.8μm~5.2μm, and further optionally 4.5μm; the composite electrode is applied to the back fine grid, and its total thickness is 2.1μm~5μm, further optionally 2.8μm~4.2μm, and further optionally 3.5μm.

[0057] In the traditional method, the thickness of the front fine grid made of silver paste is about 7μm, and the thickness of the back fine grid made of silver paste is about 5μm. In comparison, the total thickness of the composite electrode provided by the present application is lower, and the thickness as the front fine grid does not exceed 6μm, and the thickness as the back fine grid does not exceed 5μm, which can save a lot of raw materials and reduce the preparation cost, thereby achieving the effect of reducing costs and increasing efficiency.

[0058] It can be understood that the thickness of the ohmic contact layer is 0.6μm~1.5μm, and its thickness is relatively thin, so its width and aspect ratio are easy to control. After the ohmic contact layer is formed, the width of the composite electrode is fixed, so the aspect ratio of the composite electrode can be controlled by controlling the thickness of the conductive layer. The present application does not specifically limit the width of the composite electrode, and the width of the composite electrode can be adjusted according to actual production needs. In some specific examples, the composite electrode is applied to the front fine grid, and its width is 17.5μm; the composite electrode is applied to the back fine grid, and its width is 31μm.

[0059] In the present application, the ohmic contact layer is made of raw materials such as a conductive phase, a bonding phase and an organic phase; the conductive phase is the main component that affects the conductive properties of the slurry and the ohmic contact effect; the bonding phase affects the bonding strength and stability of the ohmic contact layer; the organic phase affects the viscosity and rheological properties of the system, and thus affects the construction performance and coating quality of the ohmic contact layer. By controlling the content of raw materials such as the conductive phase, the bonding phase and the organic phase, it is possible to ensure that the ohmic contact layer achieves good ohmic contact, and also to have the advantages of low series resistance, high bonding strength and stability, good construction performance and coating quality.

[0060] As an example, in the raw material of the ohmic contact layer, the mass fraction of the conductive phase is 60% to 88%, for example, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86% or 88%, and can be further selected as 80% to 85%; the mass fraction of the binding phase is 0.5% to 6%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%. or 6%, further optionally 4% to 6%; the mass fraction of the organic phase is 5% to 32%, for example 5%, 8%, 10%, 12%, 16%, 20%, 24%, 28%, 30% or 32%, further optionally 10% to 15%; the mass fraction of the functional additive is 0 to 5%, for example 0%, 0.1%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, further optionally 0.2% to 0.8%.

[0061] In the present application, the conductive phase is composed of silver powder, organic silver salt and ohmic contact metal. Among them, silver is the metal with the best conductivity, and silver powder is the main component to ensure conductivity. The conductivity of the ohmic contact metal is lower than that of the silver powder, and the difference in conductivity with the semiconductor material is small, so that the contact resistance between the ohmic contact layer and the doped polysilicon layer is small, and good ohmic contact can be achieved. At the same time, the price of the ohmic contact metal is low, which can reduce the amount of expensive silver powder and organic silver salt, thereby reducing the preparation cost of the ohmic contact layer.

[0062] The conductivity of the ohmic contact metal is worse than that of the silver powder, which will cause the series resistance of the solar cell to be too high. In order to solve the problem of excessive series resistance caused by the addition of ohmic contact metal, organic silver salts can be added to control the total resistance of the ohmic contact layer. At the same time, the organic silver salt acts as a sintering initiator, and the organic components are burned during high-temperature sintering, and the silver element is released and becomes silver atoms. Compared with silver powder, the silver atoms obtained by decomposition of organic silver salts are more active, which can drive the diffusion of silver elements throughout the sintering process, accelerate the overall reaction rate, and thus reduce the series resistance. Compared with silver powder that is insoluble in the organic phase, organic silver salts can also be dissolved in the organic phase, which is conducive to uniform distribution in the entire system, exerting a better sintering initiation effect, and making the ohmic contact layer uniform and low in series resistance.

[0063] Therefore, by controlling the mass ratio of silver powder, organic silver salt and ohmic contact metal, the contact resistance can be reduced, the ohmic contact effect can be improved, and the problem of excessive series resistance can be avoided. At the same time, the preparation cost of the ohmic contact layer can be reduced, thereby achieving the effect of reducing costs and increasing efficiency.

[0064] As an example, in the conductive phase, the mass ratio of silver powder, organic silver salt and ohmic contact metal is (45-75): (0.5-5): (5-35), wherein the value corresponding to the silver powder in the mass ratio may be 45, 50, 55, 60, 65, 70 or 75, the value corresponding to the organic silver salt in the mass ratio may be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5, and the value corresponding to the ohmic contact metal in the mass ratio may be 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32 or 35. Further optionally, in the conductive phase, the mass ratio of silver powder, organic silver salt and ohmic contact metal is (55-65): (2-4): (15-25).

[0065] Optionally, the ohmic contact metal includes one or more of zinc, aluminum, molybdenum, tantalum, titanium and tungsten.

[0066] Under the same conditions, the conductivity of common metals is arranged in the following order: silver>copper>gold>aluminum>calcium>beryllium>magnesium>zinc>molybdenum>tantalum>tungsten>titanium>manganese. If the conductivity of the ohmic contact metal is significantly different from that of the doped polysilicon layer, the potential barrier at the metal-semiconductor interface will be too high, making it difficult to form an ohmic contact. Therefore, the present application selects at least one of zinc, aluminum, molybdenum, tantalum, titanium and tungsten as the ohmic contact metal, which has a lower conductivity than gold, silver and copper, and is not much different from the conductivity of the doped polysilicon layer, which is beneficial to reducing the contact resistance and achieving good ohmic contact. In addition, the price of ohmic contact metals such as zinc and aluminum is much lower than that of silver powder, which is beneficial to reducing the preparation cost of the ohmic contact layer and solar cells, thereby achieving the effect of reducing costs and increasing efficiency.

[0067] It can be understood that the ohmic contact metal can be selected from any one of zinc, aluminum, molybdenum, tantalum, titanium and tungsten, and can also be selected from a combination of at least two of zinc, aluminum, molybdenum, tantalum, titanium and tungsten, such as zinc and aluminum, zinc and molybdenum, zinc and tantalum, zinc and titanium, zinc and tungsten, aluminum and molybdenum, aluminum and tantalum, aluminum and titanium, aluminum and tungsten, molybdenum and tantalum, molybdenum and titanium, molybdenum and tungsten, tantalum and titanium, tantalum and tungsten, titanium and tungsten, and a combination of zinc, aluminum and titanium, etc. Further optionally, the ohmic contact metal includes one or more of zinc, aluminum and titanium.

[0068] Alternatively, the organic silver salt includes silver acetate (CH3COOAg), silver trifluoroacetate (CF3COOAg), silver stearate (C 17 H 35 COOAg), silver oleate (C 17 H 33 COOAg), silver neodecanoate (C9H 19 The present invention can be one or more of silver stearate and silver neodecanoate.

[0069] Optionally, the median particle size (D50) of the conductive phase is 0.5 μm to 1.5 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm or 1.5 μm, and further optionally 0.8 μm to 1.2 μm.

[0070] If the median particle size of the conductive phase is too large, it will affect the printing effect and coating quality of the ohmic contact layer, thereby causing a loss in photoelectric conversion efficiency; if the median particle size of the conductive phase is too small, the viscosity of the system will be too low, it will not be easy to accumulate, and the fluidity will be too high, resulting in the width of the ohmic contact layer formed by printing being too large, thereby causing a loss in photoelectric conversion efficiency; at the same time, the price of the conductive phase with a small particle size is more expensive, the cost performance is low, and it is not conducive to cost reduction.

[0071] Optionally, the specific surface area of ​​the conductive phase is 0.5 m 2 / g~3m 2 / g, for example 0.5m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.2m 2 / g, 1.5m 2 / g, 1.8m 2 / g, 2m 2 / g, 2.2m 2 / g, 2.5m 2 / g, 2.8m 2 / g and 3m 2 / g, further optional to 1m 2 / g~2m 2 / g.

[0072] The specific surface area of ​​the conductive phase is controlled at 0.5 m 2 / g~3m 2 / g range, which is also helpful to control the viscosity and fluidity of the system, so that the printing effect of the ohmic contact layer is good, and the printed ohmic contact layer has a suitable width, avoiding the loss of photoelectric conversion efficiency.

[0073] It is understandable that the present application does not specifically limit the morphology of the conductive phase, which may be one or more of spherical, flaky and amorphous. Specifically, the organic silver salt will dissolve in the organic phase, and its morphology before dissolution may be powdery or granular. In some examples, both the silver powder and the ohmic contact metal are spherical structures. In other examples, the silver powder is spherical and the ohmic contact metal is flaky, or the silver powder is flaky and the ohmic contact metal is spherical. By using a combination of silver powder and ohmic contact metal of different shapes, the contact area between the particles can be increased, and the conductive properties and ohmic contact effect of the ohmic contact layer can be improved.

[0074] Optionally, the organic phase includes resin, solvent and plasticizer in a mass ratio of (0.85-4.35):(95.35-99.05):(0.1-0.3).

[0075] As an example, in the organic phase, the mass ratio of resin, solvent and plasticizer is (0.85~4.35):(95.35~99.05):(0.1~0.3) of resin, solvent and plasticizer, wherein the corresponding value of the resin in this mass ratio can be 0.85, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.2 or 4.35, the corresponding value of the solvent in this mass ratio can be 95.35, 95.5, 96, 96.5, 97, 97.5, 98, 98.5, 99 or 99.05, and the corresponding value of the plasticizer in this mass ratio can be 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28 or 0.3. Further optionally, in the conductive phase, the mass ratio of silver powder, organic silver salt and ohmic contact metal is (1-2): (97.8-98.9): (0.1-0.2).

[0076] Optionally, the resin includes one or more of polyvinyl formal (PVF), polyvinyl butyral (PVB), polyethylene terephthalate (PET), polymethyl methacrylate (PMMA), ethyl cellulose (EC), hydroxypropyl cellulose (HPC), cellulose acetate propionate (CAP), cellulose acetate butyrate (CAB), and styrene resin. Among them, the styrene resin includes one or more of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-ethylene-butylene-styrene block copolymer (SEBS) and styrene-ethylene-propylene-styrene block copolymer (SEPS).

[0077] Further optionally, the resin includes polyvinyl butyral (PVB), ethyl cellulose (EC), styrene-ethylene-butylene-styrene block copolymer (SEBS) and polymethyl methacrylate (PMMA), and the mass ratio is (0.1-0.9): (0.05-0.15): (0.5-2.7): (0.2-0.6). The value corresponding to PVB in the mass ratio can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, the value corresponding to EC in the mass ratio can be 0.05, 0.08, 0.10, 0.12 or 0.15, the value corresponding to SEBS in the mass ratio can be 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5 or 2.7, and the value corresponding to PMMA in the mass ratio can be 0.2, 0.3, 0.4, 0.5 or 0.6. In some examples, the mass ratio of PVB, EC, SEBS, and PMMA is 0.3:0.05:0.9:0.2, or 0.9:0.15:2.7:0.6, or 0.1:0.05:0.5:0.2.

[0078] Optionally, the solvent includes one or more of diethylene glycol butyl ether acetate (BCA) and 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (abbreviated as alcohol ester dodecahydrate), and further may be diethylene glycol butyl ether acetate (BCA).

[0079] Optionally, the plasticizer includes one or more of dimethyl phthalate (DMP), dimethyl adipate (DMA) and hydrogenated castor oil, and further may be hydrogenated castor oil.

[0080] Since the thickness of the ohmic contact layer is low, only 0.6 μm to 1.5 μm, no additional liquid plasticizer is required, but a resin with a plasticizing effect is used as a plasticizer. Therefore, the present application further selects hydrogenated castor oil as a plasticizer. The hydrogenated castor oil may be unmodified hydrogenated castor oil or modified hydrogenated castor oil, and the modified hydrogenated castor oil may be polystyrene-modified hydrogenated castor oil, polyamide-modified hydrogenated castor oil, polyethylene glycol-modified hydrogenated castor oil, etc., such as Thixatrol ST.

[0081] Optionally, the binder phase includes the following components in mass fractions: PbO 20%-40%, Bi2O3 10%-30%, CuO 5%-10%, SiO2 10%-20% and B2O3 15%-30%.

[0082] It can be understood that the binder phase in the ohmic contact layer is a PbO-Bi2O3 glass powder. As an example, in the binder phase, the mass fraction of PbO is 20% to 40%, such as 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38% or 40%, and can be further selected as 25% to 35%; the mass fraction of Bi2O3 is 10% to 30%, such as 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%, and can be further selected as 10% to 20%; the mass fraction of CuO is 5% to 10%, such as 5%, 5.5%, 6%, 6.5%, 7.5%, 8.5%, 9.5%, 10.5%, 11.5%, 12.5%, 13.5%, 14.5%, 15.5%, 16.5%, 17.5%, 18.5%, 19.5%, 20.5%, 21.5%, 22.5%, 23.5%, 24.5%, 25.5%, 26.5%, 27.5%, 28.5%, 29.5%, 30.5%, 31.5%, 32.5%, 34.5%, 36.5%, 38.5%, 38.5%, 35.5%, 36 ... %, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, and can be further selected as 8% to 10%; the mass fraction of SiO2 is 10% to 20%, for example, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, and can be further selected as 14% to 16%; the mass fraction of B2O3 is 15% to 30%, for example, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, and can be further selected as 25% to 30%.

[0083] Optionally, the median particle size of the binder phase is 0.5 μm to 1.5 μm, such as 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm or 1.5 μm, and further optionally 0.8 μm to 1.2 μm.

[0084] Optionally, the softening point of the adhesive phase is 250°C to 620°C, for example, 250°C, 280°C, 300°C, 320°C, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C or 620°C, and can further be 350°C to 450°C.

[0085] By controlling the composition, median particle size and softening point of the bonding phase, the bonding strength, sintering performance and uniformity of the ohmic contact layer can be improved, so that the sintered ohmic contact layer has a good ohmic contact effect and a lower series resistance.

[0086] Optionally, the functional additives include one or more of a release agent, a thixotropic agent, a defoaming agent, a dispersant, a leveling agent and an antioxidant, which can improve the printing effect, surface flatness and coating quality of the ohmic contact layer, thereby improving the performance of the solar cell.

[0087] Further optionally, the functional additive is a release agent, such as a silane release agent, a wax release agent, a fluorocarbon release agent, a polyether release agent, and a polyester release agent, etc. Among them, the silane release agent can be silicone oil, silicone rubber, etc., the wax release agent can be paraffin, microcrystalline wax, polyethylene wax, carnauba wax, etc., and the fluorocarbon release agent can be polytetrafluoroethylene, fluorosilicone resin, etc. Selecting a suitable release agent can make the entire system easy to demold and have a good printing effect.

[0088] Optionally, the method for preparing the ohmic contact layer comprises the following steps:

[0089] S110: providing an ohmic slurry containing a conductive phase, a bonding phase, an organic phase and a functional additive;

[0090] S120: Screen printing, drying and sintering the ohmic paste to form an ohmic contact layer.

[0091] In step S120, the drying temperature is 200°C to 400°C, and the sintering temperature is 700°C to 900°C. As an example, the drying temperature may be 200°C, 225°C, 250°C, 275°C, 300°C, 325°C, 350°C, 375°C, or 400°C, and the sintering temperature may be 700°C, 725°C, 750°C, 775°C, 800°C, 825°C, 850°C, 875°C, or 900°C.

[0092] Optionally, the conductive layer includes a silver layer, and a preparation method of the silver layer includes one or more of a sputtering coating method and an electroplating method, and further optionally the sputtering coating method.

[0093] Compared with the silver layer produced by screen printing and high-temperature sintering, the silver layer formed by sputtering or electroplating has good uniformity, density and adhesion, which makes the series resistance very small, which is conducive to improving the conductivity of the composite electrode. At the same time, the thickness of the silver layer formed by sputtering or electroplating is lower, and less silver is used, which can achieve the purpose of cost reduction.

[0094] Sputtering is a physical vapor deposition technology, which can be magnetron sputtering or radio frequency sputtering, and its action range is the surface of the ohmic contact layer. In some specific examples, the sputtering method includes the following steps: after forming the ohmic contact layer on the cell, the cell is placed in a vacuum chamber and evacuated; nitrogen or argon is introduced as the sputtering gas, and the flow rate and pressure of the sputtering gas are adjusted; under the action of the electric field, the silver atoms on the silver target are sputtered out and deposited on the surface of the ohmic contact layer to form a silver layer; by controlling the sputtering time, sputtering power, sputtering voltage and other parameters, the thickness and performance of the silver layer can be adjusted.

[0095] During the electroplating process, a mask is required to cover the non-electroplating area, and electroplating is performed on the surface of the ohmic contact layer. In some specific examples, the electroplating method includes the following steps: after forming the ohmic contact layer on the battery cell, a mask is formed on the non-electroplating area of ​​the battery cell, and then the battery cell is used as the cathode and placed in the electroplating tank; a silver plate or a soluble silver electrode is used as the anode and placed in the electroplating tank, corresponding to the cathode; a solution containing silver ions such as potassium silver cyanide and silver nitrate is added to the electroplating tank as an electroplating solution, so that the anode and cathode are completely immersed in the electroplating solution; the power supply is turned on, the current density and the electroplating time are adjusted, and the electroplating is performed under stirring conditions to form a silver layer of a certain thickness on the surface of the ohmic contact layer.

[0096] Optionally, the solar cell includes a silicon substrate, one surface of the silicon substrate is a front surface (light-receiving surface), and the other surface opposite to the front surface is a back surface (backlight surface);

[0097] If the solar cell is a TOPCon solar cell using single-sided poly technology, the front side of the silicon substrate includes a boron-doped emitter, a front passivation anti-reflection layer and a front electrode stacked in sequence from bottom to top; the back side of the silicon substrate includes a tunneling oxide layer, a doped polysilicon layer, a back passivation anti-reflection layer and a back electrode stacked in sequence from bottom to top.

[0098] Among them, the front electrode includes a front main grid and a front fine grid, and the back electrode includes a back main grid and a back fine grid; the back fine grid uses the composite electrode provided by the present application, and the ohmic contact layer in the composite electrode is made of ohmic slurry. Because the thickness of the ohmic contact layer is low and the conductive layer in the composite electrode does not contain a bonding phase, the bonding phase content per unit area of ​​the composite electrode is significantly reduced, and the etching effect is small, which will only damage the passivation anti-reflection layer, effectively reducing the etching degree of the doped polysilicon layer, reducing the damage to the doped polysilicon layer, which is beneficial to the improvement of the open circuit voltage, thereby improving the efficiency of the solar cell. The front fine grid can be formed by traditional silver paste printing and sintering, or the composite electrode provided by the present application can be used to further improve the battery efficiency. The front main grid and the back main grid are used to collect and conduct the photogenerated carriers in the front fine grid and the back fine grid. There is no need to achieve ohmic contact, and it can be formed by traditional silver paste printing and sintering.

[0099] If the solar cell is a TOPCon solar cell (i.e., a double-sided poly solar cell) using double-sided poly technology, the front and back sides of the silicon substrate both include a tunneling oxide layer, a doped polysilicon layer, a passivation anti-reflection layer, and an electrode stacked in sequence from bottom to top. Among them, the front electrode includes a front main grid and a front fine grid, and the back electrode includes a back main grid and a back fine grid; the front fine grid and the back fine grid both use the composite electrode provided by the present application, which causes little damage to the two doped polysilicon layers, thereby significantly improving the efficiency of the solar cell; the front main grid and the back main grid do not need to achieve ohmic contact, and can be formed by traditional silver paste printing and sintering.

[0100] Optionally, the method for preparing a double-sided poly solar cell comprises the following steps:

[0101] S210: Providing a cell, which includes a silicon substrate, and a tunneling oxide layer, a doped polysilicon layer, and a passivation anti-reflection layer sequentially disposed on two surfaces of the silicon substrate;

[0102] S220: Printing and forming an ohmic contact layer on the back and front of the battery cell respectively;

[0103] S230: Printing a back main grid on the back of the cell, forming a conductive layer on the ohmic contact layer on the back of the cell, and using the composite electrode obtained by combining the ohmic contact layer and the conductive layer on the back of the cell as a back fine grid;

[0104] S240: Printing a front main grid on the front of the cell, forming a conductive layer on the ohmic contact layer on the front of the cell, and using the composite electrode obtained by combining the ohmic contact layer and the conductive layer on the front of the cell as the front fine grid.

[0105] In addition, the composite electrode can also be applied to other types of solar cells to specifically improve the contact effect between the electrode and the doped polysilicon layer, thereby achieving the effect of reducing costs and increasing efficiency.

[0106] In a second aspect of the present application, a stacked cell is provided, comprising a bottom cell and a top cell; wherein the bottom cell is the solar cell as described above; and the top cell is a perovskite solar cell.

[0107] In a third aspect of the present application, a photovoltaic module is provided, which includes a first packaging panel, a first packaging film, a battery string, a second packaging film and a second packaging panel in a stacked arrangement, and the battery string is formed by electrically connecting a plurality of solar cells as described above, or by electrically connecting a plurality of stacked batteries as described above.

[0108] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0109] Example 1

[0110] (1) Please refer to Table 1. The ohmic paste of this embodiment includes the following raw materials in mass fractions: 83% conductive phase, 5% binder phase, 11.5% organic phase and 0.5% functional additive.

[0111] The conductive phase includes silver powder, silver neodecanoate and zinc powder in a mass ratio of 60:3:20; the D50 of the conductive phase is 0.9 μm and the specific surface area is 0.98 m 2 / g.

[0112] The binder phase is a PbO-Bi2O3 glass powder, including the following components by mass fraction: PbO 30%, Bi2O3 15%, CuO10%, SiO2 15% and B2O3 30%; the D50 of the binder phase is 1 μm and the softening point is 400°C.

[0113] The organic phase includes resin, solvent and plasticizer in a mass ratio of 1.45:98.45:0.1; the resin is a mixture of polyvinyl butyral (PVB), ethyl cellulose (EC), styrene-ethylene-butylene-styrene block copolymer (SEBS), modified hydrogenated castor oil and polymethyl methacrylate (PMMA) in a mass ratio of 0.3:0.05:0.9:0.2, the solvent is diethylene glycol butyl ether acetate (BCA), and the plasticizer is modified hydrogenated castor oil Thixatrol ST.

[0114] The functional additive is silicone oil as a release agent.

[0115] (2) Referring to Table 2, the solar cell includes a silicon substrate, and a tunneling oxide layer, a doped polysilicon layer, a passivation anti-reflection layer and an electrode sequentially disposed on two surfaces of the silicon substrate;

[0116] The electrode on the front side of the silicon substrate includes a front fine grid and a front main grid. The width of the front fine grid is 17.5 μm, the total height is 4.5 μm, and the front fine grid includes an ohmic contact layer with a thickness of 1 μm and a silver layer with a thickness of 3.5 μm. The silver layer is prepared by magnetron sputtering.

[0117] The electrode on the back side of the silicon substrate includes a back fine grid and a back main grid. The back fine grid has a width of 31 μm and a total height of 3.5 μm. The back fine grid includes an ohmic contact layer with a thickness of 1 μm and a silver layer with a thickness of 2.5 μm. The silver layer is prepared by magnetron sputtering.

[0118] (3) The preparation method of the solar cell is as follows:

[0119] A cell is provided, which comprises a silicon substrate, and a tunneling oxide layer, a doped polysilicon layer and a passivation anti-reflection layer which are sequentially arranged on two surfaces of the silicon substrate;

[0120] Using the ohmic paste of step (1), printing and forming ohmic contact layers on the front and back of the cell respectively;

[0121] The back main grid is formed by printing silver paste on the back of the cell, and a silver layer is formed on the ohmic contact layer on the back of the cell by sputtering, and the composite electrode obtained by combining the ohmic contact layer and the silver layer on the back of the cell is used as the back fine grid;

[0122] Silver paste is used to print on the front of the cell to form a front main grid, and a silver layer is sputtered on the ohmic contact layer on the front of the cell to form a silver layer, and the composite electrode obtained by combining the ohmic contact layer and the silver layer on the front of the cell is used as the front fine grid.

[0123] Embodiments 2 to 9

[0124] Please refer to Table 1. Examples 2 to 9 are basically the same as Example 1, except that the only difference is the formula of the ohmic slurry, which is as follows:

[0125] Example 2: The conductive phase includes silver powder, silver neodecanoate and zinc powder in a mass ratio of 62.5:0.5:20.

[0126] Example 3: The conductive phase includes silver powder, silver neodecanoate and zinc powder in a mass ratio of 58:5:20.

[0127] Example 4: The conductive phase includes silver powder, silver stearate and zinc powder in a mass ratio of 60:3:20.

[0128] Example 5: The conductive phase includes silver powder, silver neodecanoate and zinc powder in a mass ratio of 75:3:5.

[0129] Example 6: The conductive phase includes silver powder, silver neodecanoate and zinc powder in a mass ratio of 45:3:35.

[0130] Example 7: The conductive phase includes silver powder, silver neodecanoate, zinc powder and aluminum powder in a mass ratio of 60:3:10:10.

[0131] Example 8: The ohmic slurry includes the following raw materials in mass fractions: 63% conductive phase, 5% bonding phase, 31.5% organic phase and 0.5% functional additive; wherein the conductive phase includes silver powder, silver neodecanoate and zinc powder in a mass ratio of 45:3:15; the organic phase includes resin, solvent and plasticizer in a mass ratio of 4.35:95.35:0.3; the resin is a mixture of polyvinyl butyral (PVB), ethyl cellulose (EC), styrene-ethylene-butylene-styrene block copolymer (SEBS) and polymethyl methacrylate (PMMA) in a mass ratio of 0.9:0.15:2.7:0.6, the solvent is diethylene glycol butyl acetate (BCA), and the plasticizer is modified hydrogenated castor oil Thixatrol ST.

[0132] Example 9: The ohmic slurry includes the following raw materials in mass fractions: 87% of a conductive phase, 5% of a bonding phase, 7.5% of an organic phase and 0.5% of a functional additive; wherein the conductive phase includes silver powder, silver neodecanoate and zinc powder in a mass ratio of 63:3:21; the organic phase includes a resin, a solvent and a plasticizer in a mass ratio of 0.85:99.05:0.1; the resin is a mixture of polyvinyl butyral (PVB), ethyl cellulose (EC), styrene-ethylene-butylene-styrene block copolymer (SEBS) and polymethyl methacrylate (PMMA) in a mass ratio of 0.1:0.05:0.5:0.2, the solvent is diethylene glycol butyl acetate (BCA), and the plasticizer is modified hydrogenated castor oil Thixatrol ST.

[0133] Embodiments 10 to 14

[0134] Please refer to Table 2. Examples 10 to 14 are basically the same as Example 1, and the only difference is the thickness or preparation method of the front fine grid, which is as follows:

[0135] Example 10: The thickness of the silver layer of the front fine grid is 2.5 μm.

[0136] Example 11: The thickness of the silver layer of the front fine grid is 4.5 μm.

[0137] Example 12: The silver layer of the front fine grid is prepared by electroplating.

[0138] Embodiment 13: The thickness of the ohmic contact layer of the front fine grid is 0.8 μm.

[0139] Embodiment 14: The thickness of the ohmic contact layer of the front fine grid is 1.5 μm.

[0140] Embodiments 15 to 19

[0141] Please refer to Table 2. Examples 15 to 19 are basically the same as Example 1, and the only difference is the thickness or preparation method of the back side fine grid, which is as follows:

[0142] Example 15: The thickness of the silver layer of the back fine grid is 1.5 μm.

[0143] Example 16: The thickness of the silver layer of the back fine grid is 3.5 μm.

[0144] Example 17: The silver layer of the back fine grid is prepared by electroplating.

[0145] Embodiment 18: The thickness of the ohmic contact layer of the back fine grid is 0.8 μm.

[0146] Example 19: The thickness of the ohmic contact layer of the back fine grid is 1.5 μm.

[0147] Comparative Example 1

[0148] The solar cell structure of this comparative example is basically the same as that of Example 1, except that the front and back fine grids are formed by conventional silver paste printing and sintering, and the height of the printed front fine grid is 7 μm, and the height of the back fine grid is 5 μm.

[0149] Comparative Examples 2 to 10

[0150] Please refer to Table 1 and Table 2. Comparative Examples 2 to 10 are basically the same as Example 1, except that the differences are as follows:

[0151] Comparative Example 2: The conductive phase is all silver powder.

[0152] Comparative Example 3: The conductive phase includes silver powder and silver neodecanoate in a mass ratio of 80:3.

[0153] Comparative Example 4: The conductive phase includes silver powder, silver neodecanoate and zinc powder in a mass ratio of 40:3:40.

[0154] Comparative Example 5: The conductive phase includes silver powder and zinc powder in a mass ratio of 63:20.

[0155] Comparative Example 6: The conductive phase includes silver powder, silver neodecanoate and zinc powder in a mass ratio of 55:8:20.

[0156] Comparative Example 7: The thickness of the ohmic contact layer of the front fine grid is 0.5 μm.

[0157] Comparative Example 8: The thickness of the ohmic contact layer of the front fine grid is 1.8 μm, and the thickness of the silver layer is 2.5 μm.

[0158] Comparative Example 9: The thickness of the ohmic contact layer of the back fine grid is 0.5 μm.

[0159] Comparative Example 10: The thickness of the ohmic contact layer of the back fine grid is 1.8 μm, and the thickness of the silver layer is 2.5 μm.

[0160] Test Case

[0161] (1) Contact resistance of composite electrode: Referring to "T / CPIA 0051-2023 Crystalline Silicon Photovoltaic Cell Metal Electrode Contact Resistivity Test Method Transmission Line Model (TLM)", four parallel grid lines with a spacing of 1.04um were made, and a test fixture with a spacing of 1.04um was used for the contact resistance tester. The corresponding program transmission line model (TLM) of the contact resistance tester was selected to test the contact resistance. The results are shown in Tables 1 and 2. Among them, the parallel grid lines in Table 1 are front fine grids, which are composed of an ohmic contact layer with a thickness of 1μm and a silver layer with a thickness of 3.5μm, and the grid line width is 17.5μm; in the parallel grid lines in Table 2, the width of the front fine grid is 17.5μm, and the width of the back fine grid is 31μm. The corresponding thicknesses of the ohmic contact layer and the silver layer are shown in Table 2.

[0162] (2) Line resistance of composite electrode: The resistance value of the grid line with a fixed length of 14.5 mm is used to characterize the resistivity of the composite electrode with the same cross-sectional area.

[0163] (3) Electrical performance test of solar cells: The test was carried out using a HALM IV tester to record the open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency of the solar cells. The results are shown in Table 3.

[0164] (4) Cost reduction rate of solar cells: The cost of solar cells was calculated, and the cost of the solar cells in Comparative Example 1 was used as a reference to calculate the cost reduction rate of the solar cells in each embodiment and each comparative example. The results are shown in Table 3.

[0165] As shown in Table 1, in Examples 1 to 9, different ohmic pastes were used to prepare an ohmic contact layer with a thickness of 1 μm, and a silver layer with a thickness of 3.5 μm was sputtered on the surface. The contact resistance of the obtained composite electrode was 1.50 mΩ·cm. 2 ~1.89mΩ·cm 2 , which is significantly lower than the composite electrodes obtained in Comparative Examples 2 to 6, proving that the ohmic slurries of Examples 1 to 9 can reduce the contact resistance of the ohmic contact layer and the composite electrode to achieve a better ohmic contact effect. Among them, the contact resistance reduction effect of the composite electrode made of the ohmic slurry of Example 1 is more significant, and the amount of organic silver salt used is small, and the cost is low.

[0166] As shown in Table 2, when the ohmic slurry of Example 1 is used to prepare the composite electrode, when the thickness of the ohmic contact layer is 1 μm, the contact resistance of the front fine grid is 1.51 mΩ·cm 2 The contact resistance of the back fine grid is 0.78mΩ·cm 2 . Among them, the width of the back fine grid is greater than that of the front fine grid, so the contact resistance is lower, and the change in the thickness of the ohmic contact layer will cause a greater difference in the contact resistance of the back fine grid, but a smaller difference in line resistance. When the thickness of the ohmic contact layer is reduced to 0.8μm or increased to 1.5μm, the contact resistance of the front fine grid and the back fine grid will increase. When the thickness of the ohmic contact layer is reduced to 0.5μm or increased to 1.8μm, the contact resistance of the front fine grid reaches 2.50mΩ·cm 2 The above values ​​are significantly higher than 1.90 mΩ·cm in Comparative Example 1. 2 The contact resistance of the back side fine grid reaches 2.30mΩ·cm 2 The above is significantly higher than 1.06 mΩ·cm in Comparative Example 1. 2 , which proves that controlling the thickness of the ohmic contact layer to 0.6μm~1.5μm can effectively reduce the contact resistance of the composite electrode, and the effect of reducing the contact resistance is more significant when the thickness is 1μm.

[0167] When the thickness of the ohmic contact layer is the same, the thicker the silver layer, the lower the line resistance of the front and back fine grids, but the cost also increases. Therefore, the thickness of the silver layer of the front fine grid is controlled to 3.5μm, and the thickness of the silver layer of the back fine grid is controlled to 2.5μm, which can reduce the line resistance while avoiding excessive costs. When the thickness of the ohmic contact layer and the silver layer is the same, compared with the electroplating method, the magnetron sputtering method can obtain a silver layer with higher density, better uniformity and stronger adhesion, so the line resistance of the front and back fine grids is significantly reduced.

[0168] As shown in Table 3, the solar cells prepared in Examples 1 to 19 have an open circuit voltage of 0.7386 mV to 0.7399 mV, a short circuit current of 13.893 mA to 13.944 mA, a fill factor of 85.19% to 85.93%, a photoelectric conversion efficiency of 26.265% to 26.373%, and a cost reduction rate of 24.01% to 42.87%, which are significantly better than those in Comparative Examples 1 to 10. Among them, the photoelectric conversion efficiency of Example 1 is 26.366%, the cost reduction rate is 33.44%, and the cost reduction and efficiency improvement effect is more prominent.

[0169] Table 1. Ohmic paste formulation and contact resistance

[0170]

[0171] Table 2. Structure and preparation method of front and back fine grids

[0172]

[0173] Note: The unit of thickness is μm, and the unit of contact resistance is mΩ·cm 2 , the unit of line resistance is Ω.

[0174] Table 3. Performance test and cost of solar cells

[0175]

[0176] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0177] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.

Claims

1. A solar cell, characterized in that: It comprises a silicon substrate, and a tunneling oxide layer, a doped polysilicon layer and a composite electrode which are sequentially arranged on at least one surface of the silicon substrate; The composite electrode comprises an ohmic contact layer and a conductive layer, wherein the ohmic contact layer is located between the doped polysilicon layer and the conductive layer, and a thickness ratio of the ohmic contact layer to the conductive layer is 1:(1.5-4.5); The ohmic contact layer comprises the following raw materials in mass fractions: 60% to 88% of a conductive phase, 0.5% to 6% of a bonding phase, 5% to 32% of an organic phase, and 0% to 5% of a functional additive; The conductive phase includes silver powder, organic silver salt and ohmic contact metal in a mass ratio of (45-75): (0.5-5): (5-35), and the conductivity of the ohmic contact metal is lower than that of the silver powder.

2. The solar cell according to claim 1, wherein: The ohmic contact metal includes one or more of zinc, aluminum, molybdenum, tantalum, titanium and tungsten.

3. The solar cell according to claim 1, wherein: The organic silver salt includes one or more of silver acetate, silver trifluoroacetate, silver stearate, silver oleate, neodecanoic acid and phenyl silver.

4. The solar cell according to claim 1, wherein: The thickness of the ohmic contact layer is 0.6 μm to 1.5 μm, and the thickness of the conductive layer is 1.5 μm to 4.5 μm.

5. The solar cell according to any one of claims 1 to 4, characterized in that: The organic phase includes resin, solvent and plasticizer in a mass ratio of (0.85-4.35):(95.35-99.05):(0.1-0.3).

6. The solar cell according to claim 5, characterized in that One or more of the following conditions are met: (1) The resin includes one or more of polyvinyl formal, polyvinyl butyral, polyethylene terephthalate, polymethyl methacrylate, ethyl cellulose, hydroxypropyl cellulose, cellulose acetate propionate, cellulose acetate butyrate and styrene resin; (2) The solvent includes one or more of diethylene glycol butyl ether acetate and 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate; (3) The plasticizer includes one or more of dimethyl phthalate, dimethyl adipate and hydrogenated castor oil.

7. The solar cell according to any one of claims 1 to 4, characterized in that: One or more of the following conditions are met: (1) The binder phase comprises the following components in mass fractions: PbO 20%-40%, Bi2O3 10%-30%, CuO 5%-10%, SiO2 10%-20% and B2O3 15%-30%; (2) The median particle size of the binder phase is 0.5 μm to 1.5 μm; (3) The softening point of the adhesive phase is 250°C to 620°C.

8. The solar cell according to any one of claims 1 to 4, characterized in that: The functional auxiliary agent includes one or more of a release agent, a thixotropic agent, a defoaming agent, a dispersant, a leveling agent and an antioxidant.

9. The solar cell according to any one of claims 1 to 4, characterized in that: The method for preparing the ohmic contact layer comprises the following steps: Providing an ohmic slurry containing a conductive phase, a bonding phase, an organic phase and a functional additive; The ohmic paste is screen-printed, dried and sintered to form the ohmic contact layer.

10. The solar cell according to claim 9, characterized in that The conductive layer includes a silver layer, and a preparation method of the silver layer includes one or more of a sputtering coating method and an electroplating method.